COMPARING THE DIFFERENCE INTERPOLATION METHOD FRONT AND REAR NEWTON DIFFERENCE IN POPULATION ESTIMATE - Tri Mulyani; Hj. Latifah, SSi, MMSi Hj. Latifah, SSi, MMSi (Jurnal Sistem Informasi, 2007)
Newton interpolation method is one of the numerical methods used to estimate(predict) an amount. The author compares the difference interpolation method and thedifference behind Newton's advances in estimating the total population.Newton interpolation method produces exact answers approached (would) rather thanusing other methods listed in numerical methods.